Osseous and dental outcomes of primary gingivoperiosteoplasty with iliac bone graft: A radiological evaluation. Issue 6 (July 2015) - Touzet-Roumazeille, Sandrine; Vi-Fane, Brigitte; Kadlub, Natacha; Genin, Michaël; Dissaux, Caroline; Raoul, Gwenaël; Ferri, Joël; Vazquez, Marie-Paule; Picard, Arnaud
Abstract Primary alveolar cleft repair has two main purposes: to restore normal morphology and normal function. Gingivoperiosteoplasty with bone grafting in mixed dentition has been a well-established procedure. We hypothesized that 1) performance of this surgery in deciduous dentition would provide favorable bone graft osseointegration, and 2) would improve the support of incisor teeth eruption, thereby avoiding maxillary growth disturbances. We conducted a retrospective study of clinical and tridimensional radiological data for 73 patients with alveolar clefts (with or without lip and palate clefts) who underwent gingivoperiosteoplasty with iliac bone graft in deciduous dentition. Pre- and post-operative Cone Beam Computed Tomography (CBCT) comparison allowed evaluation of the ratio between bone graft volume and initial cleft volume (BGV/ICV ratio), and measurement of central incisor teeth movements. This series of 73 patients included 44 males and 29 females, with a mean age of 5.5 years. Few complications were observed. Post-operative CBCT was performed at 7.4 months. The mean BGV/ICV ratio was 0.62. Axial rotation was significantly improved post-operatively (p = 0.004). Gingivoperiosteoplasty with iliac bone graft is safe when performed in deciduous dentition and results in a sufficient bone graft volume to support lateral incisor eruption and upper central incisor tooth position improvement.